2012
DOI: 10.1165/rcmb.2012-0076oc
|View full text |Cite
|
Sign up to set email alerts
|

Nongenomic Effects of Fluticasone Propionate and Budesonide on Human Airway Anion Secretion

Abstract: This study investigated the physiological effects of inhaled corticosteroids, which are used widely to treat asthma. The application of fluticasone propionate (FP, 100 μM) induced sustained increases in the short-circuit current (I(SC)) in human airway Calu-3 epithelial cells. The FP-induced I(SC) was prevented by the presence of H89 (10 μM, a protein kinase A inhibitor) and SQ22536 (100 μM, an adenylate cyclase inhibitor). The FP-induced responses involved bumetanide (a Na(+)-K(+)-2Cl(-) cotransporter inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Low concentrations of DEX rapidly regulate intracellular pH, Ca 2+ and cAMP-dependent protein kinase activity, and inhibit Cl -secretion in bronchial epithelial cells via nongenomic mechanisms [11]. A recent study showed that inhaled fluticasone propionate (FP) and budesonide (BUD) stimulate cystic fibrosis transmembrane conductance regulator (CFTR)-mediated anion transport through adenylate cyclase-mediated mechanisms in a nongenomic fashion [12]. In addition to their anti-inflammatory properties, GCs attenuate ASM contractility through non-genomic effects.…”
Section: Mechanisms Of Action Of Gcmentioning
confidence: 99%
“…Low concentrations of DEX rapidly regulate intracellular pH, Ca 2+ and cAMP-dependent protein kinase activity, and inhibit Cl -secretion in bronchial epithelial cells via nongenomic mechanisms [11]. A recent study showed that inhaled fluticasone propionate (FP) and budesonide (BUD) stimulate cystic fibrosis transmembrane conductance regulator (CFTR)-mediated anion transport through adenylate cyclase-mediated mechanisms in a nongenomic fashion [12]. In addition to their anti-inflammatory properties, GCs attenuate ASM contractility through non-genomic effects.…”
Section: Mechanisms Of Action Of Gcmentioning
confidence: 99%